Effects of Adding Shiitake Stipe to Diets on Egg Quality of Hy-Line Brown Hens - Qi GAO; Yang XU; Mingyang SUN; Ao JIAO; Zhenbo SHAO; Shuangyuan LIU; Long JIAO; Youlin XUE (Shipin gongye ke-ji, 2023)
This experiment mainly studied the effect of shiitake stipe powder on the quality and nutritional composition of eggs from Hy-Line brown hens. 112 healthy 40-week-old Hy-Line brown hens in the same batch were selected and were randomly divided into 4 groups. The control group was fed the basic diet and the experimental groups were supplemented with 5%, 10% and 15% of mushroom stalk powder, respectively. After 20 weeks of feeding, the egg quality was measured. The results showed that the average egg weight and size of the experimental groups were significantly higher than those of the control group (P<0.05). The eggshells from the experimental groups were heavier, darker and redder and the eggwhite of the experimental groups were also heavier(P<0.05), the 15% addition group was the most significant. Furthermore, the nutrients in eggs of the experimental groups were higher than those in the control group, best results in the 5% addition group. On one hand, the content of lysozyme in egg white, lecithin and yolk globulin in egg yolk were significantly higher than those in the control group (P<0.05). On the other hand, the content of cholesterol in egg yolk was significantly lower than that in the control group. Furthermore, the nutrients in eggs of the experimental groups were higher than those in the control group (P<0.05), best results in the 5% addition group. On one hand, the content of lysozyme in egg white, lecithin and yolk globulin in egg yolk were significantly higher than those in the control group (P<0.05). In the experimental groups, the activity of egg yolk SOD and the DPPH free radical scavenging ability of egg white were higher. Furthermore, higher contents of aromatic volatiles were detected in the boiled egg whites and egg yolks of the experimental groups with lower nitrogen oxides in egg whites and higher umami and saltiness in egg yolks. According to sensory evaluation, the evaluators preferred the eggs of the experimental groups, because the eggs were redder and plumper with richer and purer flavor. Overall, the experimental group was generally better than the control group, with the 15% spiked group performing better in terms of egg quality and antioxidant properties, and the 5% spiked group performing better in terms of nutritional active substances and sensory characteristics.